Through moments in history : memoirs of two decades of intellectual and social life, 1970-1990 - Rahman, Md. Anisur (Muhammad Anisur) (Dhaka, Bangladesh : Pathak Shamabesh, 2007)
Memoirs of an economics professor and official of the International Labour Office (Geneva) from Bangladesh.
Includes bibliographical references (pages [273]-275) and index.
Keywords: Rahman, Md. Anisur; International Labour Organisation -- Officials and employees -- Biography; College teachers -- Bangladesh -- Biography; Bangladesh -- Politics and government -- 1971-; Bangladesh -- History -- 20th century; Bangladesh -- Intellectual life -- 20th century